Providing of the principle of right supremacy in state administration and its features in the sphere of tax relation management - Діхтієвський, Петро Васильович; Лісовська, Валентина Сергіївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
In the article the problems of realization of principle of supremacy of right on the modern stage of reformationof state administration are summarized, the priority directions of law administrative regulation ofactivity of institutions of executive power for providing of realization of principle of right of supremacy aredefined, the necessity of his fixing for a legislation which regulates tax legal relationships is grounded.